Pendekatan Holistik untuk Meningkatkan Motivasi Berhenti Merokok melalui Terapi CBT pada Siswa SMK PGRI Banyuwangi - Damayanti, Fransiska Erna; Yoelianita, Betty Erda; Rudiyanto, Rudiyanto; Sholihin, Sholihin; Toga, Ervia; Toga, Erik; Lafiya, Rifdatul; Indriani, Ninis (PPPM Stikes Banyuwangi, 2025)
Background: One of the behavioral deviations in students is smoking which has an impact on health, it is very unfortunate that even though they understand the bad effects, cigarettes are misused as a sedative and to improve mood, from the need for it related to the lack of motivation to stop smoking. Smoking behavior can be controlled by having motivation from within yourself to stop smoking. Efforts to increase motivation to stop smoking and awareness of the dangers of smoking by providing CBT therapy about the dangers of smoking. Purpose: to provide motivation related to motivation to stop smoking with Cognitive Behavioral Therapy (CBT) therapy for SMK PGRI 2 Giri Banyuwangi Students. Method: This community service activity uses lecture and demonstration methods supported by media such as PowerPoint, videos. Results: The results of this activity show an increase in knowledge from the results of the pre-test and post-test from an average score of 72.25 to 86.25. Conclusion: It is hoped that this CBT therapy can be used by teachers and school administrators in decision-making or policy-making efforts to improve smoking cessation programs for students